Evaporated Self‐Assembled Monolayer Hole Transport Layers: Lossless Interfaces in p‐i‐n Perovskite Solar Cells. Issue 8 (4th January 2023) - Farag, Ahmed; Feeney, Thomas; Hossain, Ihteaz M.; Schackmar, Fabian; Fassl, Paul; Küster, Kathrin; Bäuerle, Rainer; Ruiz‐Preciado, Marco A.; Hentschel, Mario; Ritzer, David B.; Diercks, Alexander; Li, Yang; et al.
Abstract: Engineering of the interface between perovskite absorber thin films and charge transport layers has fueled the development of perovskite solar cells (PSCs) over the past decade. For p‐i‐n PSCs, the development and adoption of hole transport layers utilizing self‐assembled monolayers (SAM‐HTLs) based on carbazole functional groups with phosphonic acid anchoring groups has enabled almost lossless contacts, minimizing interfacial recombination to advance power conversion efficiency in single‐junction and tandem solar cells. However, so far these materials have been deposited exclusively via solution‐based methods. Here, for the first time, vacuum‐based evaporation of the most common carbazole‐based SAM‐HTLs (2PACz, MeO‐2PACz, and Me‐4PACz) is reported. X‐ray photoelectron spectroscopy and infrared spectroscopy demonstrate no observable chemical differences in the evaporated SAMs compared to solution‐processed counterparts. Consequently, the near lossless interfacial properties are either preserved or even slightly improved as demonstrated via photoluminescence measurements and an enhancement in open‐circuit voltage. Strikingly, applying evaporated SAM‐HTLs to complete PSCs demonstrates comparable performance to their solution‐processed counterparts. Furthermore, vacuum deposition is found to improve perovskite wetting and fabrication yield on previously non‐ideal materials (namely Me‐4PACz) and to display conformal and high‐quality coating of micrometer‐sized textured surfaces, improving the versatility of these materials without sacrificing their beneficial properties. Abstract : Deposition of hole transport layers that utilize self‐assembled monolayers (SAM‐HTLs) has thus far been limited to solution‐based methods. Development of alternative scalable deposition methods, such as vacuum‐based evaporation techniques, is crucial to improve process flexibility. For the first time, physical vapor deposition (PVD) via thermal evaporation of widely known SAM‐HTLs (2PACz, MeO‐2PACz, and Me‐4PACz) is reported and incorporated into p‐i‐n perovskite solar cells.